Prediction of hydrophobic organic compound partition to algal organic matter through the growth cycle of Microcystis aeruginosa. (15th November 2021) - Wei, Peiyun; Fu, Heyun; Xu, Zhaoyi; Zhu, Dongqiang; Qu, Xiaolei
Abstract: Algal organic matter (AOM) is an important source for the dissolved organic matter (DOM) pool in aquatic systems, particularly in eutrophic waters. In this study, we reported the dynamic pattern of AOM hydrophobicity during the growth cycle of Microcystis aeruginosa using the partition coefficients of AOM in the aqueous two-phase system ( K ATPS ) as a simple quantitative measure. AOM hydrophobicity had significant and non-monotonic changes during the growth cycle. It increased in the lag and early exponential phases, then decreased in the late exponential and stationary phases, and rebounded in the decline phase. AOM hydrophobicity determined using the resin fractionation, SUVA254, and nuclear magnetic resonance methods shared similar non-monotonic pattern. Nevertheless, the correlations among these indicators were poor. The partition behavior of polycyclic aromatic hydrocarbons and chlorobenzenes to AOM was assessed based the K ATPS dataset and the two-phase system (TPS) model. The TPS model showed good prediction power for the partition behavior of AOM with an RMSE of 0.23, suggesting that it was applicable to AOM from Microcystis aeruginosa . Our results indicate that algae activity will influence the overall hydrophobicity of the DOM pool depending on the growth phase, resulting in changes in the bioavailability of hydrophobic organic compounds in aquatic systems. Graphical abstract: Image 1 Highlights: AOM hydrophobicity had significant and non-monotonic changes during the growth cycle. KATPS is a simple and reliable quantitative index for monitoring AOM hydrophobicity. AOM can be the more hydrophobic fraction in the overall DOM pool. The two-phase system model is applicable for predicting AOM partition behavior.